Exploring Diverse Trading Strategies in the Derivatives Market: A Comprehensive Study - Dr Ramesh Kumar Pandey, Dr. D. P. Dewangan (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
In the multifaceted derivatives trading landscape, an array of strategies beckons exploration, each offering distinct pathways to capitalize on market dynamics. This paper undertakes a comprehensive examination of these strategies, aiming to provide insights into their complexities and potential advantages. Beginning with directional strategies, the focus lies on positions tailored to the expected movement of the underlying asset's price, encompassing long and short positions, as well as versatile strategies like straddles and strangles, enabling traders to profit from bullish and bearish trends alike. Transitioning to volatility-based strategies, the spotlight shifts to capitalizing on fluctuations in market volatility rather than directional shifts, with options selling, volatility spreads, and gamma scalping serving as vehicles for exploiting changes in market uncertainty. Furthermore, arbitrage strategies take center stage, leveraging price inefficiencies across related assets or markets, with practices such as index and merger arbitrage utilized to secure risk-free profits. By dissecting and comparing these diverse trading strategies, this paper endeavors to equip traders with the knowledge and insights necessary to navigate the derivatives market adeptly, enabling them to refine their approaches and optimize strategies for enhanced trading success.